Revisitando as teorias dos ciclos de negócios de F. A. Hayek e Nicholas Kaldo - Ferreira, Tiago Brito (2019)
The debate about business cycles took an important place in the face of economic discussions in academia during the first half of the twentieth century. This paper aims to revisit Hayek and Kaldor’s business cycle theory, and the contribution of both authors to the business cycle debate. Thus seeking to draw the conclusion, from the syllogism constituted by the theoretical disparities, raised by the debate that took place within the framework of business cycle theory, which led Nicholas Kaldor, formerly a follower of Hayek, to enter the current of economic thinking that is averse to it last